2018
DOI: 10.1001/jamasurg.2017.3415
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Influence on Variation in Receipt of Contralateral Prophylactic Mastectomy for Women With Breast Cancer

Abstract: Importance Rates of contralateral prophylactic mastectomy (CPM) have markedly increased but we know little about the influence of surgeons on variability of the procedure in the community. Objective To quantify the influence of attending surgeon on rates of CPM and clinician attitudes that explained it. Design and Setting Population-based survey study in Georgia and Los Angeles County. Participants We identified 7810 women with stages 0-II breast cancer treated in 2013–15 through the Surveillance, Epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 18 publications
9
26
1
Order By: Relevance
“…Many of our findings are consistent with other studies that have examined surgeon opinion on indications for CPM, however, a notable finding from our study was the difference in CPM recommendations among the physician subspecialties. Plastic surgeons were significantly more likely to recommend CPM than other physician specialties for nearly every clinical scenario.…”
Section: Discussionsupporting
confidence: 92%
“…Many of our findings are consistent with other studies that have examined surgeon opinion on indications for CPM, however, a notable finding from our study was the difference in CPM recommendations among the physician subspecialties. Plastic surgeons were significantly more likely to recommend CPM than other physician specialties for nearly every clinical scenario.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, 59% of women who underwent NAC had sufficient downstaging for successful BCT, a proportion closer to the rate reported by van Mackelenbergh et al Katz et al demonstrated that surgeon attitude was associated with a substantial difference in the type of surgical treatment received . An estimated contralateral prophylactic mastectomy rate of 34% occurred for surgeons who least favoured initial BCT, compared with a contralateral prophylactic mastectomy rate of 4% for surgeons who most favoured BCT . This difference is consistent with the difference of more than 40% in BCT rates between the current study cohort and another Asian group undergoing NAC, demonstrating that a significant variation in BCT rates exists within study populations of similar ethnic composition and tumour sizes in Asia.…”
Section: Discussionsupporting
confidence: 89%
“…Not only is this lower than the generally expected BCT rate after downstaging suggested by Masood, it is also significantly lower than 63–68% BCT rates reported in a large multicentre study . In the current study, 59% of women who underwent NAC had sufficient downstaging for successful BCT, a proportion closer to the rate reported by van Mackelenbergh et al Katz et al demonstrated that surgeon attitude was associated with a substantial difference in the type of surgical treatment received . An estimated contralateral prophylactic mastectomy rate of 34% occurred for surgeons who least favoured initial BCT, compared with a contralateral prophylactic mastectomy rate of 4% for surgeons who most favoured BCT .…”
Section: Discussionsupporting
confidence: 78%
“…It has been suggested that decision making for CPM is highly influenced by surgeons, given their significant role in patient education [40,75,86]. The National Comprehensive Cancer Network Practice Guidelines stresses the importance of physicians creating a "shared decision-making environment" with their patients [87].…”
Section: Discussionmentioning
confidence: 99%